2002
DOI: 10.1007/s00428-002-0691-0
|View full text |Cite
|
Sign up to set email alerts
|

Expression of c-erbB2, p53, Bcl-2, Bax, c-myc and Ki-67 in apocrine metaplasia and apocrine change within sclerosing adenosis of the breast

Abstract: Molecular evidence has recently suggested a number of different pathways leading to the development of ductal carcinoma of the breast. The links between atypical ductal hyperplasia and low-grade ductal carcinoma in situ and lobular neoplasia and lobular carcinoma are well known pathologically, but high-grade in situ and invasive carcinomas appear to have a different biological oncogenetic pathway. Morphologically there is a similarity between apocrine cells and some cases of high-grade ductal carcinoma. In ord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
36
0
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 29 publications
1
36
0
1
Order By: Relevance
“…In a large body of literature, the interpretation of IHC results obtained with the use of the mouse monoclonal antibody 9E10 (from various sources) against human MYC is not straightforward because the staining that is usually reported is cytoplasmic. Presumably, the cellular location of Myc immunostaining with 9E10 varies depending on fixation conditions 36 and some groups 37 (correctly, in our view) do not consider the detection of cytoplasmic signal as a positive result. On the other hand, exclusively nuclear staining, as expected, was reported 38 with the use of the mouse monoclonal 9E11 (various suppliers).…”
Section: Myc In Normal Human Breast and Breast Cancermentioning
confidence: 74%
“…In a large body of literature, the interpretation of IHC results obtained with the use of the mouse monoclonal antibody 9E10 (from various sources) against human MYC is not straightforward because the staining that is usually reported is cytoplasmic. Presumably, the cellular location of Myc immunostaining with 9E10 varies depending on fixation conditions 36 and some groups 37 (correctly, in our view) do not consider the detection of cytoplasmic signal as a positive result. On the other hand, exclusively nuclear staining, as expected, was reported 38 with the use of the mouse monoclonal 9E11 (various suppliers).…”
Section: Myc In Normal Human Breast and Breast Cancermentioning
confidence: 74%
“…Additional immunophenotyping of the 21 carcinomas showed that with two exceptions (tumors 14 and 19), all were Bcl-2 and GATA-3 negative and several were p53 positive (Table III). There is compelling evidence indicating that benign apocrine proliferations are Bcl-2 negative (19,22); GATA-3 is a factor involved in luminal epithelial cell differentiation (46,47). Tumor 14 (15-PGDH/ACSM1 ϩ/Ϫ) contained cells that were GATA-3 positive and negative and it may correspond to a mix lesion.…”
Section: Expression Of 15-pgdh and Acsm1 In Breast Carcinomas Diagnosmentioning
confidence: 99%
“…Moreover some are positive for the gross cystic disease fluid protein-15 (GCDFP-15) (9, 24 -26), a marker that it is, however, not specific for these lesions (16,17,25). p53 expression has been observed in about 50% of invasive apocrine carcinomas (19,27), and there have been some reports addressing the characteristics of apocrine lesions using loss of heterozygosity (22,28,29) and comparative genome hybridization (10,30).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…И aER и pER сходным образом связываются с эстроген-респонсивным элементом (ERE) ДНК, активируя транскрипцию ERE-регулируемых генов. Однако в зависимости от подтипа рецептора различные промотеры реагируют на эстрогеновую стимуляцию по-разному: aER активирует, а PER угнетает транскрипцию при связывании с комплексами АР-1, SP-1 или белками цАМФ-респонсивного элемента (CRB) [23,30,46]. Показано также, что при патологической пролиферации соотношение aER/pER в ткани молочной железы изменяется: доля aER возрастает, а доля PER уменьшается [49,52,54].…”
unclassified